1994
DOI: 10.1093/rheumatology/33.9.853
|View full text |Cite
|
Sign up to set email alerts
|

Psoas Abscess in Rheumatoid Arthritis—an Inperspicuous Diagnosis

Abstract: Primary or secondary psoas abscess is infrequently seen but should not be forgotten. We report on two patients with RA who presented predominantly with back pain and who subsequently developed pyrexia. The correct diagnosis of psoas abscess was not immediately apparent. These cases and the discussion and comments which follow illustrate the difficulties that may be encountered and remind readers of this inperspicuous diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
7
0
5
Order By: Relevance
“…In the secondary type, underlying causative factors are identified and the abscess is usually caused by enteric bacteria such as E. coli and Bacteroides 4–6 . Mycobacterium tuberculosis infection of the spine, Pott's disease, is currently the most frequent cause of secondary psoas abscess in developing countries 4 7. The commonest associated conditions in secondary type are Crohn's disease, diverticulitis, appendicitis, colorectal cancer, urinary tract infection, vertebral osteomyelitis, mycotic abdominal aortic aneurysm and endocarditis 4–6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the secondary type, underlying causative factors are identified and the abscess is usually caused by enteric bacteria such as E. coli and Bacteroides 4–6 . Mycobacterium tuberculosis infection of the spine, Pott's disease, is currently the most frequent cause of secondary psoas abscess in developing countries 4 7. The commonest associated conditions in secondary type are Crohn's disease, diverticulitis, appendicitis, colorectal cancer, urinary tract infection, vertebral osteomyelitis, mycotic abdominal aortic aneurysm and endocarditis 4–6.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory investigations, in general, are not specific in diagnosing psoas abscess. Leucocytosis, elevated C reactive protein, anaemia and raised erythrocyte sedimentation rate are frequently reported 7 10. Blood cultures may be positive, and some reviews refer to positivity in about 50% of patients 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterium tuberculosis infection of the spine, known as Pott's disease, is the most frequent cause of secondary psoas abscess in developing countries. [6] Other conditions associated with secondary psoas abscess include Crohn's disease, diverticulitis, appendicitis, colorectal cancer, urinary tract infection, vertebral osteomyelitis, mycotic abdominal aortic aneurysm, endocarditis, and history of instrumentation in or around the spine. Bilateral psoas abscess occurs in just 3% of all cases, primary or secondary.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding psoas abscesses associated with autoimmune disease, Isdale et al 8 reported only two patients with a psoas abscess in RA. However, some patients with autoimmune diseases may have psoas abscesses when they suffer from fever of unknown origin.…”
Section: Discussionmentioning
confidence: 99%